Educação e resistência : o acesso ao ensino superior para mulheres negras da comunidade quilombola Santa Terezinha em Irituia/PA - NASCIMENTO, Ana Paula Vieira do (2023)
This article stems from some problematizations developed in the discipline History of Brazilian and Amazon Education of the Pedagogy course at UFPA, Abaetetuba campus, Polo de Tomé Açu and presents as its central theme Access to Higher Education by Quilombola Women in the community of Santa Terezinha in the municipality from Irituia/PA. It proposes as an objective to discuss the historical conditions of access to higher education for 4 black women from the aforementioned quilombo. The main question that drivesthe present study isto address the historical conditions that enabled the aforementioned women from the quilombo in question to access and even stay in higher education. At the methodological level, the study is anchored in a bibliographic research supported by semi-structured and documentary interviews. The results indicate that, of the four women interviewed, only one did not complete the higher education course, only one is working professionally in her training and one has already finished her academic credits and is in the phase of completion of the course. And the other has already completed two graduations, but so far does not work in their areas of training.